Experimental Investigation into Multistage versus Conventional Triaxial Compression Tests for a c-phi Soil - Shahin, Mohamed; Cargeeg, A. (Trans Tech Publications, 2011)
The procedure for conventional triaxial compression (CTC) test requires three separate soil specimens to be examined to failure under different confining pressures so that Mohr-Coulomb (or stress path) failure envelope can be determined and soil shear strength parameters can be obtained. An alternative procedure is the multi-stage triaxial (MST) compression test, which requires only one soil specimen to be tested at three stages of shearing with different confining pressures. There are several advantages for using MST over CTC, which apart from fewer soil specimens, include less laboratory time consumption and reduced effects of heterogeneity among the specimens tested. However, it has been argued in the literature that the advantages of using MST may be compromised by its inability to obtain reliable soil behavior or accurate shear strength parameters. In this paper, the accuracy of MST compared to CTC is investigated for a c-phi soil, and a simple procedure that can be adopted to rectify the MST results is proposed.